SYNTHESIS OF PASSIVATING STRUCTURES OF MULTILAYER THIN-FILM RESISTORS - V.S. Mamontov; S.A. Gurin; M.D. Novichkov; D.V. Agafonov; K.L. Zakirova (Измерение, мониторинг, управление, контроль)
Background. The relevance of this study is related to the development of radioelectronic equipment, which requires improvement of the electrical parameters of electronic components, including time and temperature stability. Materials and methods. The processes occurring in the structure of thin films leading to a change in the resistance of a thinfilm resistor over time are investigated. Results. The technology of synthesis of thin-film resistors with a protective coatingand the parameters determining the materials of thin films and their sequence are presented. Conclusions. The developed technology makes it possible to achieve values of TCR of thin-film resistors in the range ± 3 1/ °C.